Pentingnya Peran Sekolah Dalam Pendidikan Politik Bagi Siswa Tentang Kajian Berita Hoax Di Indonesia - Kris Yunianto; Marlina Dea; Dimas Yeni; Anita Trisiana (Universitas Slamet Riyadi, 2020)
The junior high school is an institution used for the activities of learn of teachers as well as the river subsides be left to be liberal and generous has so far obtained teaching subject corresponding to its field. School would be one of the places where to educate anak-anak with a view to give the science which is given to be they can be useful for a nation and country. This study aims to to see how the role of of the schools in political education. The fact that there are official middle east news agency hoax in indonesia quite disturbing and extremely dangerous for the community especially students of becoming professional actors , in order to do this schools are obliged to increase political awareness students. Was used in the study a method of descriptive of it is anticipated that analysis. The role of school showed that school is the role of most important education for made by media political education that can be educate political students via with the program political education both through subjects pkn, osis activities, extracurricular, and the form of other activities that planned manner and is open to give political information to students.